A Framework of Islamic Architecture: An Architectural Reviews of Four Studies - Muhammad Ismail Hasan; Asrul Mahjuddin Ressang Aminuddin; Previari Umi Pramesti (LPPM bekerja sama dengan Prodi Teknik Sipil, Arsitektur, Perencanaan Wilayah dan Kota, Desain Interior, dan Desain Komunikasi Visual Universitas Pradita, 2025)
This study attempts to expand the critical indicators of Islamic architecture from four objects by different scholars. Those four objects give various aspects in terms of location and function in Islamic architecture. The first object is a lesson learned from the Prophet Mosque as the prototype of an urban element introduced by the Prophet and an Islamic architecture object outright. The second object is the Arabs’ houses, where Islamic civilization grew and became a learned lesson object of housing. The third object is a traditional Islamic settlement in Central Java, Majasto, with a dynamic interaction between the cemetery, Mosque, and settlement. The last object is a study on Muslim houses in Australia, on how they deal with and adapt their house to Muslim needs. From those four object studies, it generates four main points in Islamic architecture, encompassing design fosters faith, promoting green building, social connectedness, and maintaining privacy. The study is expected to contribute to existing knowledge of Islamic architecture by providing various object studies as the framework.